At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
and...what is (f^-1)'(3)? Soooooo confusing!!!!
f(x) = (e^x) + (4x^1/3)
How did you find that?
integration and derivated from e^x is e^x integration from (4/3)x^(-2/3) is (-2/3 +1)=1/3 then (4/3)/(1/3)= 4x^1/3
So, you just simply integrate the original equation?
f'(x) means first derivative from f(x) to find f(x) you have to integrate it
When you integrate don't you get e^x+4x^(1/3)?
alright and then that is just simply f(x) right?
f(1) means change x with 1
Okay. How would I exactly find the inverse of f(x)?
Follow this example. f(x) = (x+3)/5 To find its inverse, write y=f(x) y= (x+3)/5 Interchange x and y x = (y+3)/5 solve for y in terms of x 5x=y+3 y=5x-3 The inverse of f(x) is f^-1(x) = 5x-3
I got this far...x=e^y+4y^(1/3) and now I'm stuck.
log both side log x = y + 1/3 log 4y
Then you get lnx=y+(1/3)ln4+(1/3)lny?
isn't it ln x = y + 1/3 ln 4y, i dont understand this, confused too
Well, I was thinking that you would add because usually when you have a product in a ln then that means you add. right?
i made mistake, for example 2 ln 2y = ln 4y^2 so 4y^1/3 = 1/3 * 4 ln y
Okay, thank you.